Commit 0d7562df authored by ian@well-typed.com's avatar ian@well-typed.com

Accept T3208b output following unicode quotes change

parent 05cd20d9
T3208b.hs:15:10:
Could not deduce (STerm o0 ~ STerm a)
from the context (OTerm a ~ STerm a, OBJECT a, SUBST a)
bound by the type signature for
fce' :: (OTerm a ~ STerm a, OBJECT a, SUBST a) => a -> c
at T3208b.hs:14:9-56
NB: `STerm' is a type function, and may not be injective
The type variable `o0' is ambiguous
Expected type: STerm o0
Actual type: OTerm o0
Relevant bindings include
fce' :: a -> c (bound at T3208b.hs:15:1)
f :: a (bound at T3208b.hs:15:6)
In the expression: fce (apply f)
In an equation for fce': fce' f = fce (apply f)
T3208b.hs:15:15:
Could not deduce (OTerm o0 ~ STerm a)
from the context (OTerm a ~ STerm a, OBJECT a, SUBST a)
bound by the type signature for
fce' :: (OTerm a ~ STerm a, OBJECT a, SUBST a) => a -> c
at T3208b.hs:14:9-56
The type variable `o0' is ambiguous
Relevant bindings include
fce' :: a -> c (bound at T3208b.hs:15:1)
f :: a (bound at T3208b.hs:15:6)
In the first argument of `fce', namely `(apply f)'
In the expression: fce (apply f)
In an equation for fce': fce' f = fce (apply f)
T3208b.hs:15:10:
Could not deduce (STerm o0 ~ STerm a)
from the context (OTerm a ~ STerm a, OBJECT a, SUBST a)
bound by the type signature for
fce' :: (OTerm a ~ STerm a, OBJECT a, SUBST a) => a -> c
at T3208b.hs:14:9-56
NB: ‛STerm’ is a type function, and may not be injective
The type variable ‛o0’ is ambiguous
Expected type: STerm o0
Actual type: OTerm o0
Relevant bindings include
fce' :: a -> c (bound at T3208b.hs:15:1)
f :: a (bound at T3208b.hs:15:6)
In the expression: fce (apply f)
In an equation for ‛fce'’: fce' f = fce (apply f)
T3208b.hs:15:15:
Could not deduce (OTerm o0 ~ STerm a)
from the context (OTerm a ~ STerm a, OBJECT a, SUBST a)
bound by the type signature for
fce' :: (OTerm a ~ STerm a, OBJECT a, SUBST a) => a -> c
at T3208b.hs:14:9-56
The type variable ‛o0’ is ambiguous
Relevant bindings include
fce' :: a -> c (bound at T3208b.hs:15:1)
f :: a (bound at T3208b.hs:15:6)
In the first argument of ‛fce’, namely ‛(apply f)’
In the expression: fce (apply f)
In an equation for ‛fce'’: fce' f = fce (apply f)
Markdown is supported
0% or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment